The role of social media in immigrants' response to xenophobic violence in South Africa - Borman, Jan Willem (My University, 2018)
Xenophobia and other forms of discrimination and prejudice has long been a problem in South Africa. When it reached a boiling point in 2008, the country could have been forgiven for thinking that the worst has happened. But since then the country has seen incident after incident and wave after wave of violence against foreigners. Despite all of these incidents, research around xenophobia and responses to it has neglected spending time focusing on the victims themselves. There are bodies of research exploring the responses of government, civil society and other institutions such as the police to xenophobia. By failing to examine the responses of immigrants to xenophobia, research treats them as passive victims. Through resistance and attempts to fight back against the perpetrators of xenophobic violence in recent years, we know that is not the case. Migrants and migrant communities have agency and are active role players in society. Mobilising and responding to xenophobic violence might take different forms including traditional forms such as word of mouth at regular places of gathering and the use of social media. This research not only examines the responses of immigrants to xenophobic violence, but also examines the role social media plays in responding to xenophobic violence.
A thesis submitted in partial fulfillment of the requirements for the degree of Masters in Migration and Displacement Studies, School of Social Sciences, Faculty of Humanities, University of the Witwatersrand, September 2018
Keywords: Xenophobia--South Africa; Violence--South Africa; Immigrants--Violence against--South Africa